2019
DOI: 10.14295/ras.v33i4.29532
|View full text |Cite
|
Sign up to set email alerts
|

Hidrodinâmica do Sistema Aquífero Cárstico Bambuí, com uso de traçadores corantes, na região de Lagoa Santa, Minas Gerais

Abstract: A área estudada localiza-se a 30 km a norte de Belo Horizonte e engloba a Área de Proteção Ambiental Carste de Lagoa Santa. A Formação Sete Lagoas é a principal unidade aflorante, configurando uma geomorfologia cárstica diversa, caracterizada por canyons, vales cegos, dolinas e cavernas. Em subsuperfície, uma rede de condutos forma aquíferos cársticos que abrigam importantes reservas hídricas, que vêm sofrendo riscos qualitativos e quantitativos face a acentuada pressão da expansão demográfica e industrial. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The values of transmissivity found by De Paula et al (2020) also vary greatly, with a median value of approximately 10 −4 m 2 /s. In contrast, Teodoro et al (2019) found values exceeding 6.0 m/s for hydraulic conductivity in conduits, which, if converted to transmissivity, would be around 500 m 2 /s. It is important to note that these speeds were measured through direct observations of known routes using dye tracers and may be representative of large conduits that function as underground rivers in the mature karst aquifer of the region.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The values of transmissivity found by De Paula et al (2020) also vary greatly, with a median value of approximately 10 −4 m 2 /s. In contrast, Teodoro et al (2019) found values exceeding 6.0 m/s for hydraulic conductivity in conduits, which, if converted to transmissivity, would be around 500 m 2 /s. It is important to note that these speeds were measured through direct observations of known routes using dye tracers and may be representative of large conduits that function as underground rivers in the mature karst aquifer of the region.…”
Section: Resultsmentioning
confidence: 88%
“…The units of the Bambuí Group, which dominate the region, have moderate to high degree of deformation. Fracture families, thrust faults, horizontal foliation, and shear zones (Ribeiro et al, 2003) influence the erosive processes responsible for the tertiary karst porosity of the carbonate terrain (Teodoro et al, 2019). In addition, there is a greater dissolution along bedding planes and vertical fractures, which influence the widening of conduits along the main directions of groundwater flow (NW‐SE, W‐E, and SW‐NE) (Auler, 1994; Ribeiro et al, 2019).…”
Section: Geological and Hydrogeological Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados de condutividade hidráulica para o aquífero cárstico, obtidos pela aplicação da lei de Snow, mostraram ordem de grandeza semelhantes aos encontrados por Teodoro et al (2019). Portanto, se averigua a presença de um fluxo de água subterrânea controlado por condutos nas porções mais rasas do aquífero (aquífero cárstico) e um fluxo mais profundo controlado, principalmente, por fraturas (aquífero cárstico-fissural).…”
Section: Conclusõesunclassified
“…6). In order to test the adherence of the mathematical method to calculate the return time proposed by Ferrari and Karmann (2008), the results obtained for the Gordura stream were compared to the results found by Teodoro et al (2019) in their tracer trials in the same basin. The former encountered a 23-hour delay between launch and reception of dye tracers in this basin.…”
Section: Time Series Analysismentioning
confidence: 99%